Royal reels : enhancing the customer experience for slot machines and beyond - Grayson, Kent, (SAGE knowledge. Cases., 2016)
CEO Richard Gedman has suddenly found himself running two separate but potentially related businesses: the slot manufacturing and marketing business that he has been running for years, and a new online and mobile gaming business that has grown incredibly fast over the past couple of years. To sustain success in both businesses, it seems clear that each one will require significant R&D investments. Should he invest in only one or both?